Peningkatan Pemahaman Konsep Sistem Koordinat Melalui Metode Tutor Sebaya pada Siswa Kelas VI SDN Bendogerit 2 Kota Blitar - Sri Kusanti (Civiliza Publishing, 2022)
Mathematics as structured knowledge, where properties and theories are made deductively based on defined or undefined elements and based on proven axioms, properties, or theories. Mathematics is also defined as a language of symbols about various ideas using defined terms. carefully, clearly and accurately. In the UPT Education Unit of SDN Bendogerit 2, Blitar City, there is a lack of cooperation with peers, this causes a lack of improvement in learning outcomes for students who are less intelligent. It can be seen in the initial learning that group and individual results are obtained, in group results from 5 groups only 1 group is complete or 20%, while in individual results from 20 students only 7 students or 35% have not achieved mastery of the material according to the KKM 75%. For this reason, classroom action research is needed using appropriate learning methods. The method used is the Peer Tutor Method which is a learning strategy that utilizes students who have privileges, intelligence and skills in the classroom to help provide explanations, guidance and direction to other students whose intelligence is somewhat lacking or slow in receiving lessons of almost the same age or classmate.